2019
DOI: 10.1101/679845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PTMProphet: Fast and Accurate Mass Modification Localization for the Trans-Proteomic Pipeline

Abstract: Spectral matching sequence database search engines commonly used on mass spectrometry-based proteomics experiments excel at identifying peptide sequence ions, and in addition, possible sequence ions carrying post-translational modifications (PTMs), but most do not provide confidence metrics for the exact localization of those PTMs when several possible sites are available. Localization is absolutely required for downstream molecular cell biology analysis of PTM function in vitro and in vivo. Therefore, we deve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Using the PTMProphet tool (50) which is built into FragPipe and has recently been tailored to localize any assigned modifications, we assessed the probability score for localization and found that for most peptides the localization probability is greater than 0.8 (Figure 3E).…”
Section: Sp3-rox Analysis Ofmentioning
confidence: 99%
“…Using the PTMProphet tool (50) which is built into FragPipe and has recently been tailored to localize any assigned modifications, we assessed the probability score for localization and found that for most peptides the localization probability is greater than 0.8 (Figure 3E).…”
Section: Sp3-rox Analysis Ofmentioning
confidence: 99%
“…Existing tools for open search postprocessing perform a limited set of analyses on a spectrumlevel basis. PTM-Prophet (13), for example, is limited to localizing mass differences for each PSM but does not provide data summaries that can inform subsequent searches nor does it provide identities for mass differences. Philosopher (14) only provides mappings of mass differences to UniMod and generates a basic mass shift histogram.…”
Section: Introductionmentioning
confidence: 99%
“…When only a few (if any) fragment ions can be observed in MS2 spectra that distinguish the different localization possibilities, it becomes increasingly more difficult to locate the modification site accurately (26). It should be noted that database search algorithms such as Andromeda from MaxQuant and Mascot by Matrix Science also suffer from this issue (27), and other more dedicated software packages can be used to resolve such ambiguities at least partially (28)(29)(30)(31). We chose to retain such ambiguous phosphopeptide spectra clusters because we deem these to contain valuable information for further biology-centered data analysis.…”
Section: Discussionmentioning
confidence: 99%